Study of Various Methods of Biodiesel Production and Properties of Biodiesel Prepared from Waste Cotton Seed Oil and Waste Mustard Oil - Singh, Sandeep (My University, 2012)
Biodiesel, an alternative fuel is derived from the fats of animals and plants. As energy demand increases and fossil fuels are limited, research is directed towards alternative renewable fuels. Besides exploring historical background of biodiesel production from vegetable oils, it also provides insight of different methodologies evolved for the conversion of vegetable oil in biodiesel. Properties of waste edible oil (cotton seed oil and mustard oil) have been compared with the properties of petro-diesel; showing a comparable regime for satisfactory optimized blend which is to be selected for the better performance of a C.I. engine with biodiesel. Biodiesel reportedly has number of technical advantage over petro-diesel especially on safety and environmental considerations. Cold starting, clogging and storage are some serious technological disadvantages associated with biodiesel. The work presented in this thesis is mainly divided into two main parts. In the first part study of different methods of production of biodiesel (direct blending, transesterification, pyrolysis and micro emulsion) from waste cooking oil is to be examined. The most commonly used method is transesterifcation of vegetable oils and animal fats. The transesterifcation reaction is affected by molar ratio of glycerides to alcohol, catalysts, reaction temperature, reaction time and free fatty acids and water content of oils or fats. The second part includes the study of characteristics of biodiesel prepared from vegetable oils (waste cotton seed oil and waste mustard oil).The characteristics of biodiesel are to be checked at different blends(B10, B15, B20) and select the optimum blend based on these characteristics. The characteristics include FFA value, density, viscosity, flash point and fire point, cloud point and pour point, carbon residue content and ash residue content.
Master of Engineering (Thermal Engineering)
Keywords: Waste cottonseed oil; waste mustard oil; transesterification; characterisation